Antibiotic Stewardship in Disaster Situations: Lessons Learned in Lebanon - Anita Shallal; Chloe Lahoud; Marcus Zervos; Madonna Matar (Antibiotics, 2022)
A post-prescription review and feedback program was implemented as an antimicrobial stewardship intervention in Lebanon as the country grappled with complete economic collapse, the COVID-19 pandemic, and a large blast in Beirut. We describe the implications of antimicrobial use in disaster preparedness and crisis situations, the sequelae related to increasing antimicrobial resistance, and our lessons learned in Lebanon. We explore opportunities and potential solutions for future disaster preparedness.